Affordances of musical instruments: Conceptual consideration - Tullberg, Markus (Frontiers in Psychology, 2022)
While the concept of affordances has been applied in music research, it has not been satisfyingly developed regarding musical instruments. The resulting vagueness restricts the potential of the concept to guide exploration, discussion, and development of new approaches towards musical learning. Also, the concept of affordances comes with strong ontological claims and thus prompts the researcher to be careful when merging it with other theoretical domains or applying it in empirical studies. Consequently, the present article aims at contributing to a conceptualization of affordances of musical instruments by highlighting and discussing components that are necessary to consider in such a project. The first part consists of an overview of key elements of ecological psychology and more recent theoretical contributions, which are of relevance to the aim of the article: Material Engagement Theory, Skilled Intentionality Framework, and Sensorimotor Contingency Theory. A brief review of examples on how the concept of affordances has been applied in music research is presented. The main section of the article discusses four components, vital to further theoretical developments on affordances of musical instruments: the musical niche, spatial networks, sensorimotor relationship, and the amodal nature of affordances. Central to the argument is an understanding of affordances as relational, limited in scope and bound up with the physical interaction between musician and instrument. Accordingly, it is proposed that analytical focus in studies of musical instruments should be the sensorimotor relationship, spatiotemporally unfolding through a musical event. The article is concluded with comments upon educational implications of the presented perspective and suggestions on further research on the topic.